Avaliações celulares, moleculares e endócrinas na reprodução de Myotis levis machos (Chiroptera: Vespertilionidae) - Talita de Oliveira Farias (2021)
The vespertilionid Myotis levis is a neotropical insectivorous bat, which presents a seasonal reproductive pattern, characterized by a cyclic fluctuation of reproductive organs along the year. Considering its ecological importance and unique reproductive strategies, this study aimed to investigate the cellular, molecular, and endocrine aspects involved in M. levis reproduction. The adult male bats were captured from M. levis colony located in RPPN Santuário do Caraça, Minas Gerais, Brazil. The gonads, epididymides, accessory sex glands, brown adipose tissue, and blood were collected to perform biometric, histological, morphometric, immunostaining and hormonal analyses. Moreover, testis fragments and brown adipose tissue were used for xenografting in immunodeficient mice. As results, after a rainfall peak, a significant increase of testis mass and spermatogenesis development of M. levis occurs in the Maturing and Mature stages. In the Mature stage, a fast and elevated sperm production occurs associated with an increase in nuclear diameter and volume of Leydig cells, maximum expression of the steroidogenic 3-Beta-HSD enzyme, and elevated testosterone serum levels of M. levis. During these periods, the brown adipose tissue is consumed, supporting testosterone synthesis (proven through brown adipose tissue xenograft). In the Regressed stage, epididymis and accessory sex gland masses reach higher values. The spermatozoa remain stored in epididymis cauda for eight months. The sperm concentration, vitality, and motility presented high rates in the Regressed stage; however, the higher incidence of normal morphological gametes occurred in the mating period (Rest stage). After performing the xenograft of testis fragments, we realize that spermatogenesis progressed until the spermiogenic phase in all reproductive stages in a recipient model with stable hormonal levels. These data reinforced the influence of seasonality and hormonal variation in M. levis reproduction. The new information concerning the reproductive cycle of M. levis and the use of tissue xenografts are vital for understanding the reproduction of neotropical vespertilionids. The studies about bat reproduction are crucial for the ecological and economic aspects. Besides being bioindicators, bats can control insect populations that cause damage to crop and promote disease dissemination in the population.